Methylmercury Impact on Adult Neurogenesis: Is the Worst Yet to Come From Recent Brazilian Environmental Disasters? - Raposo, Ramon da Silva; Pinto, Daniel Vieira; Moreira, Ricardo; Dias, Ronaldo Pereira; Fontes Ribeiro, Carlos Alberto; Oriá, Reinaldo Barreto; Malva, João Oliveira (Frontiers in Aging Neuroscience, 2020)
Worldwide environmental tragedies of anthropogenic origin causing massive release of metals and other pollutants have been increasing considerably. These pollution outbreaks affect the ecosystems and impact human health. Among those tragedies, recent large-scale environmental disasters in Brazil strongly affected riverside populations, leading to high-risk exposure to methylmercury (MeHg). MeHg is highly neurotoxic to the developing brain. This toxicant causes neural stem cell dysfunction and neurodevelopmental abnormalities. However, less is known about the effects of MeHg in the postnatal neurogenic niche, which harbors neural stem cells and their progeny, in the adult brain. Therefore, taking in consideration the impact of MeHg in human health it is urgent to clarify possible associations between exposure to mercury, accelerated cognitive decline and neurodegenerative diseases. In this perspectives paper we discuss the neurotoxic mechanisms of MeHg on post-natal neurogenesis, and the putative implications associated with accelerated brain aging and early-onset cognitive decline in populations highly exposed to this environmental neurotoxicant.